Can We Enhance Passivity with a Surface Finish? Spectroscopic and Electrochemical Analysis on 316L Stainless Steel. Issue 1 (27th January 2022) - Neupane, Shova; Zanna, Sandrine; Seyeux, Antoine; Klein, Lorena H.; Maurice, Vincent; Marcus, Philippe
Abstract : The effects of surface finish by mechanical polishing, vibratory polishing, and high-temperature annealing were studied on 316L stainless steel by combining microscopic and spectroscopic analysis of the surface morphology and composition and electrochemical analysis of the corrosion resistance. Compared to mechanical polishing, vibratory finishing promotes passivity at the active-passive transition in acid solution and enhances resistance to chloride-induced passivity breakdown. Cr and Mo enrichments in the native oxide film increase owing to preferential iron etching. The bilayer structure develops a thicker Cr(III) oxide inner barrier layer and an outer exchange layer further enriched in Cr(III) hydroxide and Mo(IV/VI) oxides. The Fe-rich weak sites of passivity are reinforced. High-temperature annealing in reducing hydrogen environment enables us to fully reconstruct the cold-worked layers left by mechanical or vibratory finishing, thus allowing us to expose the bulk microstructure at the topmost surface. The benefits brought by vibratory finishing are lost upon reducing the initial native oxide. The re-formed native oxide develops a bilayer structure with similar Cr and Mo enrichments as that obtained from mechanical polishing and no beneficial effects on passivity. The results provide comprehensive insight into how the passivity of stainless steel can be enhanced by surface enrichment engineering.